2018
DOI: 10.15587/1729-4061.2018.139674
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study into optimal interdependence of energy-time costs for emptying a dry dock

Abstract: Оцiнений вплив дискретних властивостей мiкропроцесорної системи управлiння на основi Arduino Due на точнiсть фiзичної моделi докової насосної станцiї шляхом моделювання в MATLAB. При цьому враховувалися такi чинники, як перiод комутацiї ШIП, крок квантування по рiвню i за часом АЦП i ЦАП мiкропроцесора, час виконання програмного циклу, шум молодших розрядiв АЦП, шум i iнерцiйнiсть датчика струму, а також вiдхилення параметрiв ємнiсних фiльтрiв, включених в канали зворотного зв'язку по напрузi, вiд номiнальних … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Thus, the major energy consumers at the stations are the main pumps, which in most cases are equipped with direct-on-line unadjustable-speed induction motor drive. Meanwhile, in [3,4] it is shown that by switching to adjustable-speed drive of the main pumps, it is possible to achieve significant energy savings in the process of chamber emptying. In addition, it is possible to adjust the supply at the stage of final guidance of the vessel before fitting on the dock set and at low levels of water table in the chamber.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the major energy consumers at the stations are the main pumps, which in most cases are equipped with direct-on-line unadjustable-speed induction motor drive. Meanwhile, in [3,4] it is shown that by switching to adjustable-speed drive of the main pumps, it is possible to achieve significant energy savings in the process of chamber emptying. In addition, it is possible to adjust the supply at the stage of final guidance of the vessel before fitting on the dock set and at low levels of water table in the chamber.…”
Section: Introductionmentioning
confidence: 99%